Sediment Transport Analysis of Sesayap River, Malinau District, North Kalimantan - Hardhi Rafsanjani (Journal of the Civil Engineering Forum, 2017)
River could have a very important role in improving the economy of a country when it is correctly and properly utilized. Nevertheless, rivers in Indonesia also have various problems, i.e. erosion and sedimentation which occur in many Indonesian rivers, one of it being the Sesayap River. Because of these problems, it is very important to do analysis on bed load transport, in order to find its amount in the existing river, so that optimal handling on the occurring erosion and sedimentation problems could be performed. This research aimed to obtain the amount of bed load transport in Sesayap River, and then compare it to the field condition. The approaches used in this bed load transport analysis were Einstein approach and Frijlink approach, with data required for the analysis, which was water level elevation, topography data, and sediment gradation data. Based on the result of conducted bed load transport analysis, the bed load transport analysis result in Seluwing area was higher than in the Port area. Therefore, sediment deposition or sedimentation would occur in the river segment on between both locations. Qualitatively or tendentiously, the above results showed consistency with what actually happened, or observed, in the field. If it assumed that the equivalent diameter of bed load is 8 mm, the total of bed load transport on Seluwing area and Port area with Einstein approach are 1,582,263 m3 and 1,219,181 m3. Therefore, the sedimentary deposit per day could be calculated by calculating difference of bed load transport volume divided with total of the calculation day; which resulted sedimentary deposit per day of 2,859 m3. Whereas by using the Frijlink approach, the total of bed load transport on Seluwing area and Port area were of 1,391,940 m3 and 1,080,200 m3, and sedimentary deposit per day of 2,455m3. Based on the results, in order to normalize the Sesayap River, the dredging needed is 2,859m3/day based on Einstein approach and 2,455m3/day based on Frijlink approach.